PERSPEKTIF LITERASI DIGITAL BAGI GURU SEKOLAH DASAR - Sutan Saribumi Pohan; Suparman Suparman (SEUNEUBOK LADA: Jurnal ilmu-ilmu Sejarah, Sosial, Budaya dan Kependidikan, 2020)
In general what is meant by literacy is a set of abilities and skills of individuals in reading, writing, speaking, counting and solving problems at a certain level of expertise needed in daily life, in Latin called literatus means learning, so that literacy is language learning. When correlated with digital literacy, it means that the ability to use computer technology both responds to the existence of information through the internet and can access, analyze and communicate information ethically, tolerantly, responsibly, rationally and respecting human rights principles. Elementary school teachers who gain access to education from various aspects of training, seminars, symposiums, teacher group work (KKG), as well as learning through libraries and independently will be involved with progress and development in the field of technology that cannot be separated from digital literacy as one of the elements in develop the perspective of elementary school teachers who bring opportunities as a teaching system that adapts to the various momentum that develops in society, for example teaching with blanded learning models, online learning, web tutorials, web learning, synchronous academic interaction, computer mediaced classes, technology enhanced learning, resources sharing, and virtual learning environment. This article discusses 1) Norms and elementary school teachers as scientists 2) Respond to new ideas through digital literacy with the aim of welcoming the informatics-based curriculum in 2021 from elementary to high school level. The conclusion is that elementary school teachers will be involved in teaching digital literacy in the classroom with a variety of scopes and problems, including building a harmonious and characterized society through digital literacy in the hope that it can use technology as a teaching vehicle implemented by teachers in reaching individuals as a nation of character or as center of character strengthening, because the current era of the younger generation is very familiar with digital and social media via the internet.